(untitled) (Economics and region, 2022)
The aim of the study is to highlight the influence of the intensification of bank lending to industrial enterprises on the improvement of the macroeconomic environment on the example of Saudi Arabia. The attractiveness of the example of Saudi Arabia can be explained by the following circumstances: the country is an energy superpower, which in recent decades has been directing its efforts to overcome the dependence of financial revenues on oil exports; the development of banking business in Saudi Arabia, in particular bank lending operation to industrial enterprises, has developed relatively recently – since the second half of the XX century. Special attention is paid to the contribution of national development bank, a specially created financial institution, the Saudi Industrial Development Fund, in promoting structural transformations in the national economy. The article answers the following scientific questions: 1) What are the scale, dynamics and main trends of bank lending to industrial enterprises in Saudi Arabia, and their impact on the macroeconomic environment of the country; 2) What structural changes have taken place in the national economy of Saudi Arabia after the intensification of bank lending to industrial enterprises; 3) What lessons for developing countries can be reached from the experience of Saudi Arabia, in particular in terms of cooperation between development banks and industry.